A construção de um discurso humanista em Gilberto Freyre: elementos para uma concepção relativista sobre os direitos humanos - Araújo, Erika Maria Magalhaes Avila de (2015)
This dissertation analyzes the construction of a humanist discourse in Gilberto Freyre. This research starts from the assumption that there are elements in freyreano’s thought to act as an indicator of a relativistic conception of human rights, regardless he was not a jurist, nor have dealt objectively with legal issues and human rights, Gilberto Freyre has a theoretical knowledge who contributes to legal discourse, considering a master's degree in social and legal sciences, in Columbia, at which time he had contact with the cultural anthropology of Franz Boas. At first, as a way to introduce the theoretical debate, there is the definition of which texts bring this concern to the legal field. Then, realize that the discussion around the bachelor’s degree behavior, in the nineteenth century, and the aim of making the legal education closest of social changes through legal sociology, evidences the construction of a relativistic discourse on human rights. Thus, a historical positioning becomes imperative on the period in which the “freyreanas” research will be carried out, bringing the sociological theories in vogue at the time and the development of sociology as a science, to situate the cultural relativism of Franz Boas. The methodology of Boas’s research, peculiar in the conduct of social research, puts Boas as a transforming landmark for sociology as a science, as it brings to this science the empirical character through cultural anthropology. A next step is to understand the influence of Boas’s studies on the development of humanistic-contextual theory of Gilberto Freyre. That is, the dissertation intends to analize in which way the Boas’s empirical trend approaches the Gilberto Freyre’s thoughts about the relativist discourse on human rights. It’s possible to identify the humanistic-contextual aspects that justify the existence of the relativistic humanistic thought in the “freyreanas” sociological analyzes.Thus, to resolve the theoretical-literature concern, the deductive method was used to situate Gilberto Freyre in a historical context, identifying contextual and humanistic elements in Boas analysis, which influences the formation of a Freyre’s legal culture in human rights.